Gambaran Enuresis pada Anak Sekolah Dasar - Tumbal, Anastasya G.; Umboh, Adrian; Rompis, Johnny L. (e-CliniC, 2026)
Abstract:  Enuresis is defined as involuntary voiding in children aged ≥5 years, occurring at least twice per week for three consecutive months, and not attributable to underlying medical conditions. Enuresis is influenced by biological, psychological, and environmental factors and remains commonly observed among primary school children. This study aimed to describe the occurrence of enuresis and its associated risk factors among elementary school children at Paal Dua District. A quantitative descriptive design with a cross-sectional approach was used. Samples were obtained through proportionate stratified random sampling from 250 respondents enrolled in SD Advent 3 Paal Dua, SD GMIM 22 Manado, and SD Advent 6 Kairagi Weru. Data were collected using the Clinical Management Tools (CMT) questionnaire from the Indonesian Urological Association and a previously validated and reliable research instrument. The findings showed that among the 15 children with enuresis, most were six years old (66.7%) and male (60%). The highest percentages were found in enuresis occurred predominantly at night (93.3%), the onset began since birth (66.7%), and voided 4–7 times per day (93.3%). The most frequently identified risk factors included toilet training at 3–4 years of age (73.3%), difficulty being awakened from sleep (53.3%), urinary tract infection complaints (33.3%), psychological stress (20%), and a history of constipation (26.7%). A family history of enuresis was present in 60% of cases, and the most common household composition was four family members (33.3%). In conclusion, enuresis remains present among primary school children in Paal Dua District, indicating the need for early detection and continuous parental education. Keywords: enuresis; elementary school children; nocturnal enuresis; risk factors    Abstract: Enuresis merupakan pengeluaran urin secara involunter pada anak usia ≥5 tahun dengan frekuensi minimal dua kali per minggu selama tiga bulan berturut-turut tanpa disebabkan oleh kondisi medis tertentu. Enuresis dipengaruhi oleh faktor biologis, psikologis, dan lingkungan, serta masih sering ditemukan pada anak sekolah dasar. Penelitian ini bertujuan untuk menggambarkan kejadian enuresis dan faktor risikonya pada anak sekolah dasar di Kecamatan Paal Dua. Jenis penelitian ialah deskriptif kuantitatif dengan desain potong lintang. Sampel diperoleh melalui teknik proportionate stratified random sampling dari 250 responden yang berasal dari SD Advent 3 Paal Dua, SD GMIM 22 Manado, dan SD Advent 6 Kairagi Weru. Instrumen penelitian menggunakan kuesioner Clinical Management Tools (CMT) dari Ikatan Ahli Urologi Indonesia serta instrumen penelitian sebelumnya yang telah diuji validitas dan reliabilitasnya. Hasil penelitian menunjukkan dari 15 anak dengan enuresis, sebagian besar berusia 6 tahun (66,7%) dan berjenis kelamin laki-laki (60%). Persentase tertinggi didapatkan pada kejadian enuresis terutama terjadi pada malam hari (93,3%), onset enuresis sejak lahir (66,7%), dan frekuensi berkemih 4–7 kali per hari (93,3%). Faktor risiko yang paling banyak ditemukan meliputi toilet training pada usia 3–4 tahun (73,3%), sulit dibangunkan saat tidur (53,3%), keluhan infeksi saluran kemih (33,3%), riwayat stres (20%), serta riwayat sembelit (26,7%). Riwayat enuresis dalam keluarga ditemukan pada 60% anak, dan komposisi keluarga terbanyak adalah empat anggota dalam satu rumah tangga (33,3%). Simpulan penelitian ini ialah enuresis pada anak sekolah dasar di Kecamatan Paal Dua masih cukup sering ditemukan sehingga diperlukan upaya deteksi dini dan edukasi berkelanjutan kepada orang tua. Kata kunci: enuresis; anak sekolah dasar; enuresis nokturnal; faktor risiko